THE EFFECT OF CORN COB COMPOST APPLICATION ON GROWTH AND YIELD OF OKRA (Abelmhoscus esculentus L) IN ALLUVIAL SOIL - Weking Rikardo Butar Butar,Elly Mustamir,Tatang Abdurrahman, Weking Rikardo (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aimed to determine the effect of corn cob compost application on the growth and yield of okra in alluvial. This research was conducted from October 2018 to December 2018 in the experimental garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. The study used a completely randomized design (CRD) method with one factor, which consisted of 5 treatments with 5 replications and each replication consisted of 4 sample plants. The treatment were is K1 = 6% corn cob compost or equivalent to 291 g / polybag, K2 = 8% corn cob compost or equivalent to 583 g / polybag, K3 = 10% corn cob compost or equivalent to 875 g / polybag, K4 = 12% of corn cobs compost or equivalent to 1,168 g / polybag and K5 = 14% corn cob compost or equivalent to 1,459 g / polybag. The variables observed in this study included root volume,leaf area, plant dry weight, flowering age, plant dry weight, number of fruits per plant and weight of fruit per plant. The results of the study showed that the application of corn cob compost at a dose of 10% or equivalent to 875 g / polybag was effective influence on the variables of root volume, leaf area, plant dry weight, flowering age, and fruit weight plant. Keywords: alluvial, compost, corn cob, okra